THE INFLUENCE OF ECONOMIC LITERATURE, SELF-CONTROL, AND PEOPLE GROUP ON CONSUMPTION BEHAVIOR OF STUDENTS FACULTY OF ECONOMICS, JAKARTA STATE UNIVERSITY, CLASS 2017 - Rachmah, Ratu Aulia; Sariwulan, Rd. Tuty; Nurjanah, Siti (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2021)
The purpose of this study was to determine how the influence of economic literacy on consumptive behavior, self-control on consumptive behavior, peer groups on consumptive behavior, and how the influence of economic literacy, self-control, and peer groups on consumptive behavior in students of the Faculty of Economics, State University of Jakarta, class of 2017. The methods used in this study are correlation research and quantitative approaches. The results of this study indicate that (1) economic literacy has no significant effect on consumptive behavior, (2) self-control has a significant effect on consumptive behavior, (3) peer groups have a significant effect on consumptive behavior, (4) and together economic literacy, self-control, and peer groups have an effect significant to consumptive behavior.